Intra- and inter-metropolitan variations of racial income inequality - Silveira, Leonardo Souza (2014)
What is the income gap between blacks and whites within the same metropolitan region? What variable puts individuals in greatest disadvantage: skin color or place of residence? Should mitigating policies against inequality be global or local? To answer these questions we compare the wages of blacks and whites living in the center and in the periphery of six Brazilian metropolitan regions. Results from the PNAD (2008) show that the impact of skin color on wages is larger than that of the geographic location within the city. We also show that there is substantial spatial heterogeneity in income differentials by race.